Biodiversity of Mangrove Brachyuran Crabs of Family Ocypodidae and Sesarmidae in Koto XI Tarusan District, West Sumatera, Indonesia - Kamal, Eni; Yuspardianto; Wulandari, Dwieke Putri; Fitriyani; Lubis, Amelia Sriwahyuni (HAYATI Journal of Biosciences, 2024)
The Mangrove ecosystem is an ecosystem that is around the edge of the coast and many organisms live in this ecosystem, one of them is crabs. The crabs that are often found are deposit crabs from the Ocypodidae and Sesarmidae families that act as balancers in the mangrove ecosystem. This study aimed to analyze species, diversity, evenness, and dominance in the mangrove vegetation area of Koto XI Tarusan District, West Sumatera, Indonesia. The method used is the descriptive method. The biodiversity of brachyuran crabs’ families, Ocypodidae and Sesarmidae, was analyzed with the Shannon-Wiener index (H’). Four indices were calculated for crabs Ocypodidae and Sesarmidae: species identification, Shannon-wiener (H’) diversity, evenness, and dominance indices. The results showed that there were six species of deposited crabs from the Ocypodidae and Sesarmidae families, namely Uca bellator, U. rosea, Perisesarma eumolpe, P. plicatum, Sarmatium germaimi, and Sesarma curoense. The most abundant species (Di) came from the family Sesarmidae. However, for all stations, diversity (H') has a value that is in the medium category, and evenness (E) is in the high category at each station. The dominance (D) obtained a value categorized as low at each observation station. The condition of environmental parameters in the mangrove vegetation area is included in the category of a good environment. It is still within normal limits for the crabs of the Ocypodidae and Sesarmidae families to live. Two substrate types are found in each observation path: muddy and sandy mud.